Does the Internet Need a Hegemon?. Issue 3 (14th August 2017) - Rovner, Joshua; Moore, Tyler
Abstract: Hegemonic stability theory holds that a dominant power can produce international cooperation by providing public goods and resolving collective action dilemmas. Successful hegemons also resist the temptation to exploit their advantages in order to reduce other states' fear of domination. This article asks whether or not the internet needs the United States to play a similar role. If so, Washington should pursue policies designed to strengthen internet security while eschewing espionage and cyberattacks that rely on some degree of internet insecurity. If not, it can go on the offensive without fear of undermining the system as a whole. We examine the technical and political fallout from revealed offensive cyberoperations to assess the relative fragility of the internet. Our findings suggest that it is relatively resilient.